Spatio-temporal correlation based fast inter mode decision for HEVC - Wei ZHU; Xun-hua ZHANG; Cai-sheng WANG; Hua2 ZHANG (Tongxin xuebao)
The new generation high efficiency video coding (HEVC) standard adopts coding tree unit (CTU) quadtree partition technology and ten inter prediction unit (PU) modes to improve compression efficiency significantly, but it brings in an enormous encoding computational complexit . A spatio-temporal correlation based fast inter mode decision algorithm for HEVC was proposed to reduce partition times of coding unit (CU) and inter PU mode candidates. First, the spatio-temporal correlation of depth information among the current CTU, the same located CTU in the reference frame and the spatial neighbor CTU in the current frame are utilized to predict depth range of the current CTU. Then, the spatial correlation of optimal PU modes between the current CU and its parent-CU was analyzed. And the rate-distortion (RD) costs of the estimated PU modes of the current CU were also used. Based on these, the redundant inter PU modes of current CU are skipped. The experiment results demonstrate that as compared to the HEVC test model (HM), the proposed algorithm saves about 52% encoding time under different encoding configurations, and it maintains a good RD performance. When compared to HM with fast mode decision algorithms enabled, the proposed algorithm further saves about 30% encoding time.